The prevalence of the sesamoid bones of the hand - Yammine, Kaissar (2014)
The literature contains various estimates of the prevalence and distribution of the sesamoid bones in the hands. The aims of this systematic review are to provide a better estimate of the frequency of hand sesamoids and its association with variables such as ancestry, gender, and side. Nineteen studies met the inclusion criteria. The pooled rates of the sensitive meta‐analyses from large‐sample studies in adults showed: (a) true overall rates of 99.9% for the metacarpophalangeal (MCP) joint of the thumb (MCP‐I), 53% for the interphalangeal joint (IP‐I), 43.4% for the MCP of the index (MCP‐II), 1.47% for the MCP of the medius finger (MCP‐III), 0.6% for the MCP of the ring finger (MCP‐IV), and 67.7% for the MCP of the auricular finger (MCP‐V); (b) true radiological rates of 99.9% for the radial thumb sesamoid, 99.6% for the ulnar thumb sesamoid, 47.8% for IP‐I, 40% for MCP‐II, 1.3% for MCP‐III, 0.8% for MCP‐VI, and 62.8% for MCP‐V. Black, Middle Eastern, and European ancestries conferred significantly higher sesamoid frequencies at IP‐I, MCP‐II, and MCP‐V, respectively. There was a significant association with female gender at MCP‐II, MCP‐IV, and MCP‐V, with ORs of 1.53, 4, and 1.3, respectively, and a nonsignificant “female” trend for the other locations. There was no significant association with hand side. The pooled rates of hand sesamoids in children aged 10–17 years were 92.7, 42.2, 33.8, 0.5, 0.3, and 36.5% for MCP‐I, IP‐I, MCP‐II, MCP‐III, MCP‐IV, and MCP‐V, respectively. The findings of this evidence‐based anatomical review provide quantitative evidence that the incidence of sesamoid bones in human hands depends on genetic rather than functional factors